INCREASING OF GLYCOSAMINOGLYCAN AND HYDROXYPROLINE CONTENT IN RAT CARTILAGE MANDIBLES AFTER INSULIN LIKE GROWTH FACTOR–I INDUCTION: PENINGKATAN GLIKOSAMINOGLIKAN DAN HIDROKSIPROLIN PADA TULANG RAWAN MANDIBULA TIKUS SETELAH INDUKSI INSULIN LIKE GROWTH FACTOR-I - I Gusti Aju Wahju Ardani (Dentika: Dental Journal, 2012)
The cellular effects of Insulin Like Growth Factor-I (IGF-I) are mediated by binding to cell IGF-I receptors, which arefound mainly on cells of mesenchymal origin, such of fibroblast, chondrocytes, and osteoblast. The study suggests thatIGF-I may regulate chondrocytes proliferation, differentiation and extracellular matrix deposition. The purpose of thisstudy was to quantify a synthesis of hydroxyproline HYP and glycosaminoglycan (GAG) by primary chondrocyteculture with IGF-I at 0, 5, 25, and 50 ng/ml concentration. Chondrocyte proliferation was assessed with collagensynthesis and measured by using hydroxyproline (HYP) assay and glycosaminoglycan GAG synthesis was determinedwith dimethylmethylene blue dye binding assay for 10 days. Primary chondrocytes was cultured for 10 days with 0, 5, 25and 25 ng/ml IGF-I. The results showed that, IGF-I was a potent in increasing GAG synthesis and also effective inpromoting collagen HYP synthesis. At the 50 ng/ml concentration, IGF-I was upregultators of GAG synthesis, producing6 times more GAG than control. Collagen content was promoted by IGF-I at its lower concentration, with level 3 timeshigher than control. In conclusion, IGF-I at doses ranging from 5 to 50 ng/ml for ten days has proved the induction GAGand HYP synthesis in 10 days primary chondrocyte culture of secondary cartilage rat condyles.